Gastrointestinal drug delivery - Hua, Susan (Henry Stewart Talks, 2021)
Anatomy of the gastrointestinal tract, Principles of drug absorption in the gastrointestinal tract, Physiological and pharmaceutical factors influencing drug delivery, Routes for drug delivery in the gastrointestinal tract, Drug targeting in the stomach, small intestine, and colon